Ambient air pollution and birth outcomes: a scoping review to investigate the mediating and moderating variables—protocol - Amy Mizen; Richard Fry; Lucy Perry; Kate Ellis-Davies; Amy Isham (BMJ Open)
Introduction Pregnant women and their babies are a highly vulnerable population to health effects from air pollution. This scoping review aims to understand the extent and type of evidence concerning the mediating and moderating factors between air pollution and birth outcomes. By gathering and synthesising this evidence, this review aims to identify key concepts, themes and knowledge gaps. In turn, these findings will serve as a valuable resource for researchers and policymakers by highlighting potential pathways and gaps in evidence.Methods and analysis This scoping review protocol is based on the Joanna Briggs Institute (JBI) methodology for scoping reviews and will be reported in full with a Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping review (PRISMA-ScR) flow diagram. This review will search eight databases: Web of Science, Scopus, PubMed, Embase, GreenFILE, CINAHL Ultimate, APA PsycINFO and MIDIRS. Results will be limited to those written or translated into English and peer-reviewed studies with no restriction on publication date. The study selection and data extraction will be completed within the software Covidence by two or more independent reviewers, with conflicts solved by group discussion. The data extracted from this process will include publication details, study characteristics and population characteristics.Ethics and dissemination This study will not collect primary data; therefore, no formal ethical approval is required. The findings will be disseminated to academic and non-academic audiences through conferences, publications and focus groups.Trail registration number Open Science Framework (https://doi.org/10.17605/OSF.IO/6Y2D9).